2008
DOI: 10.1177/0165025408089268
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of self-concept among Ethiopian immigrant and Israeli-born children and adolescents

Abstract: This article reports a study comparing self-concept among 114 immigrant children and adolescents of Ethiopian origin in Israel and among 164 native-born Israelis, including an exploration of how age, gender, and first-language proficiency affect various dimensions of this construct. For the younger children (aged 8-9 years), self-concept was found to be higher among the native-born than among children of Ethiopian origin, while for junior high school children (aged 14-15 years), results were reversed. Findings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…No consensus has been reached on the effects of age, race, and gender on self-concept across the entire age-span (Wilson, 1998). The results of several studies to date on this topic have been contradictory because previous studies have shown a continued decrease in various dimensions of self-concept during the transition from childhood to adolescence (Tannenbaum, 2008). Therefore, age may be an important factor related to the self-concept of adolescents.…”
Section: Introductionmentioning
confidence: 95%
“…No consensus has been reached on the effects of age, race, and gender on self-concept across the entire age-span (Wilson, 1998). The results of several studies to date on this topic have been contradictory because previous studies have shown a continued decrease in various dimensions of self-concept during the transition from childhood to adolescence (Tannenbaum, 2008). Therefore, age may be an important factor related to the self-concept of adolescents.…”
Section: Introductionmentioning
confidence: 95%
“…The Ethiopian Jewish community came to Israel with a deep Jewish identity and a rich culture and heritage, with a prominence of strong social networks and an emphasis on the extended family and values of respect ( Schwarz, 2016 ). However, on coming to Israel, difficulties in integration resulted from deep cultural differences ( Kaniel, 1990 ; Tannenbaum, 2008 ), such as the transition from poor rural living to an urban society, significant illiteracy and a more patriarchal culture with religious and community leaders acting as high authority ( Kurman and Ronen-Eilon, 2004 ), as well as racism and discrimination on the basis of skin color ( Offer, 2007 ). Two major waves of immigration took place in 1984 and 1991, with continued immigration into the 21st century.…”
Section: Introductionmentioning
confidence: 99%
“…For Ethiopian immigrants, difficulties in integration have resulted from deep cultural differences (Kaniel, 1990; Tannenbaum, 2008). Following the 1973 recognition of their Jewish status (Ben-David & Ben-Ari, 1997), emigration of the Jewish community began (Ben-Ezer, 2005).…”
Section: Introductionmentioning
confidence: 99%